Genetics of tumor metastasis 2 - Weinberg, Robert (Henry Stewart Talks, 2015)
Re-examining the stem-cell tumor model, Interconvertibility between non-stem cells and stem cells, The key for generating cancer stem cells (CSCs) from non-cancer stem cells, Filopodium-like structures (FLPs) in metastatic cancer, Mechanistic link between epithelial/mesenchymal transition (EMT) & the CSC state